2016
DOI: 10.3389/fphar.2016.00198
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Anti-Candidiasis Mediated Wound Healing Property of Cymbopogon nardus Essential Oil on Chronic Diabetic Wounds

Abstract: Poor wound healing is one of the major complication of diabetic patients which arises due to different factors like hyperglycemia, oxidative stress, vascular insufficiency and microbial infections. Candidiasis of diabetic wounds is a difficult to treat condition and potentially can lead to organ amputation. There are a few number of medications available in market to treat this chronic condition; which demands for alternative treatment options. In traditional system of medicine like Ayurveda, essential oil ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 32 publications
4
23
0
2
Order By: Relevance
“…Consistent with these existing studies, the current finding of the inhibitory effect of LEO on inflammatory biomarkers indicates that it may possess anti-inflammatory properties and modulate the tissue remodeling process in pre-inflamed human dermal fibroblast cells. Moreover, the anti-inflammatory activity of LEO, along with its anti-proliferative effect in human skin cells, might promote enhanced wound healing, presumably via acceleration of proper tissue remodeling processes [19] .…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these existing studies, the current finding of the inhibitory effect of LEO on inflammatory biomarkers indicates that it may possess anti-inflammatory properties and modulate the tissue remodeling process in pre-inflamed human dermal fibroblast cells. Moreover, the anti-inflammatory activity of LEO, along with its anti-proliferative effect in human skin cells, might promote enhanced wound healing, presumably via acceleration of proper tissue remodeling processes [19] .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, their use in topical therapy seems to be most reasonable, e.g., in the treatment of the wounds or ulcers complicated by polymicrobial infections. Interesting study in this respect has been presented by Kandimalla et al [ 23 ] who reported anti- Candida and anti-inflammatory property of citronella oil in diabetic wound healing. Similar optimistic report published by Warnke et al [ 24 ] concerns anti-bacterial activity of EOs mixture (mainly based on eucalyptus oil) in patients with incurable head and neck cancer and associated malodorous necrotic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA kits from R&D systems, USA were used to measure the serum pro inflammatory cytokines TNF-α and IL-1β. Each sample was done in duplicate and results were expressed in Pg/ml ( Kandimalla et al, 2016b , c ).…”
Section: Methodsmentioning
confidence: 99%